A Finite Element Based Optimization Algorithm to Include Diffusion into the Analysis of DCE-MRI - Sainz-DeMena, Diego; Ye, Wenfeng; Pérez, María Ángeles; García Aznar, José Manuel (Jornada de Jóvenes Investigadores del I3A, 2022)
DCE-MRI is a widly used technique to obtain a quantitative description of the tumour vasculature. Contrast agent diffusion has a great impact on the extraction of this descriptors. This work presents a new approach based on the FEM to account for this phenomenon. The proposed model outperforms the state-of-art models.